All-Solid-State Electrochromic Device Based on Nanocellulose/PANI/PEDOT Ternary Hybrid System for High Optical Contrast and Excellent Cycling Stability. Issue 2 (2nd February 2019) - Zhang, Sihang; Chen, Sheng; Zhao, Yinghui; Kang, Jian; Chen, Jinyao; Yan, Bin; Gu, Yingchun; Yang, Feng; Cao, Ya
Abstract : In this work, we present a novel all-solid-state electrochromic device based on a nanocellulose(NC)/polyaniline(PANI)/poly(3, 4-ethylenedioxythiophene)(PEDOT) hybrid film system. This ternary hybrid system was composed of the rod-like NC/PANI/PEDOT nanocomposites with a core/shell structure using NC as matrix material and PANI and PEDOT as coating electrochromic functional components, which was prepared via in situ chemical oxidative polymerization. The resultant ternary NC/PANI/PEDOT core/shell nanorod film shows significant optical contrast (61% at 665 nm), short response time (1.2 s for coloring, 1.3 s for bleaching), high coloration efficiency (214.5 cm 2 /C) and good cycling stability (sustaining 85.6% of its initial contrast after subjecting 5000 s). Moreover, the all-solid-state electrochromic device (ECD-NPE) is successfully fabricated by assembling NC/PANI/PEDOT and PEDOT: poly(styrenesulfonate)(PSS) films as the anode and cathode, respectively. Large contrast ratio, fast switching speed, high coloration efficiency and excellent cycling stability (optical contrast decay of only 4.7% after cycling 5000 s) are achieved by the assembled ECD-NPE. The fascinating electrochromic device exhibits promising features for a wide range of applications in buildings, airplanes, automobiles, etc.